Phenotypic characterization of idiopathic epilepsy and epilepsy of unknown cause in Irish Setters - Plonek, Marta; Diaz-Espineira, Montse M.; Stassen, Quirine E. M.; Santifort, Koen M.; Leegwater, Peter A. J.; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2022)
Canine epileptic seizures are common neurological symptom presenting to veterinary practice. Idiopathic epilepsy (IE) with a suspected genetic background has been reported in several dog breeds. Although it has been reported in the Irish Setter (IS), the phenotypic characteristics have not yet been described. The aim of this study was to characterize the phenotype of IE in this breed and to trace its mode of inheritance. Owners of IS were requested to fill in a questionnaire via the Dutch Irish Setter Club concerning the epileptic seizures in their dogs. The data was assessed retrospectively using descriptive statistics. Forty-eight privately owned IS dogs fulfilling tier I criteria for IE according to the International Veterinary Epilepsy Task Force of both sexes were included in the study. The mean age of seizure onset was 41 months. Five of the dogs included in the study had an onset of seizures > 6 years of age. These dogs were classified with epilepsy of unknown cause (EUC). Primary generalized tonic-clonic seizures were the most common type of seizure and were seen in almost all dogs. Cluster seizures were reported in 54% of the studied population. Most owners reported pre- (56%) and post-ictal (97%) signs in their dogs. A pedigree analysis of one subpopulation was performed and traced the lineage of 13 affected IS. A segregation analysis of this population rejected a simple autosomal recessive inheritance pattern. The present study supports the occurrence of IE and EUC in the IS. The results provide clinical insight into epileptic seizures in this breed and may be a starting point for further, including genetic, analysis.